KINERJA KARYAWAN DI SEKOLAH MENENGAH PERTAMA: APAKAH DIPENGARUHI OLEH THE BIG FIVE PERSONALITY, PRODUKTIVITAS KARYAWAN, DAN WORK ENGAGEMENT? [EMPLOYEE PERFORMANCE IN JUNIOR HIGH SCHOOLS: IS IT INFLUENCED BY THE BIG FIVE PERSONALITY, EMPLOYEE PRODUCTIVITY, AND WORK ENGAGEMENT?] - Qodariah, Qodariah (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2025)
In the current global era, an employee is required to be more professional in working. As is known, human resources are the part that supports and implements every process within the organization. Seeing SMP Negeri 32 Kota Tangerang which has a vision of